DIGITAL HEALTH INTERVENTIONS TO IMPROVE GLYCEMIC OUTCOMES IN TYPE 2 DIABETES MELLITUS: A LITERATURE REVIEW - Utomo, Waras Budi; Muzdalipah; Muhajir, Reska Ahmad; Fawzi, Yulianur (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Type 2 diabetes mellitus (T2DM) is a growing global health concern marked by persistent hyperglycemia and a high risk of complications. Despite advancements in treatment, many patients fail to achieve optimal glycemic control. Digital health interventions (DHIs) have emerged as promising tools to support self-management and improve outcomes in T2DM care. This literature review aims to evaluate the effectiveness of DHIs in enhancing glycemic control among individuals with T2DM. A literature review was conducted by searching databases such as EBSCOhost, ScienceDirect, ProQuest, and Google Scholar for full-text articles published between 2016 and 2025. Inclusion criteria focused on studies involving adult T2DM populations using mobile apps, telemedicine, or web-based platforms to support glycemic management. A total of 10 studies met the criteria and were analyzed narratively. A total of 10 studies were analyzed in this literature review to evaluate the impact of digital health interventions on glycemic control among T2DM patients. These studies comprised randomized controlled trials, quasi-experimental studies, and cohort studies conducted in various global settings. The findings consistently demonstrated that digital health interventions such as mobile applications, web-based platforms, and telemedicine systems positively affect glycemic control, primarily measured through decreased HbA1c levels. This literature review concludes that DHIs show strong potential in improving glycemic control in T2DM. The effectiveness of these interventions is influenced by user engagement, digital literacy, and integration with healthcare support.